Acaulospora flava, a new arbuscular mycorrhizal fungus from Coffea arabica and Plukenetia volubilis plantations at the sources of the Amazon river in Peru - Corazon Guivin, Mike Anderson; Vallejos Tapullima, Adela; De la Sota Ricaldi, Ana María; Cerna Mendoza, Agustín; Guerrero Abad, Juan Carlos; Santos, Viviane Monique; Da Silva, Glandstone Alves; Oehl, Fritz (Julius Kühn-Institut, 2021)
A new arbuscular mycorrhizal fungus, Acaulospora flava, was found in coffee (Coffea arabica) and inka nut (Plukenetia volubilis) plantations in the Amazonia region of San Martín State in Peru. The fungus was propagated in bait cultures on Sorghum vulgare, Brachiaria brizantha and Medicago sativa as host plants. It differentiates typical acaulosporoid spores laterally on sporiferous saccule necks. The spores are light yellow, bright yellow to yellow brown, (95-)105-160 × (95-)100-150 μm in diameter and have smooth spore surfaces. Phylogenetically, A. flava clusters in a well-separated clade, nearest to A. kentinensis, followed by A. herrerae, A. spinosissima, A. excavata and A. aspera, of which remarkably A. spinosissima, A. excavata and A. aspera had also been found in inka nut plantations of San Martín State during the last years. Here, we report also A. herrerae and A. fragilissima as fungal symbionts within the rhizosphere of coffee and the inka nut. The later two fungi had so far been recorded by concomitant morphological and molecular analyses only from tropical islands, A. herrerae from Cuba in the Golf of Mexico and A. fragilissima from New Caledonia in the southwest Pacific Ocean close to Australia. In this study, the ITS region of A. herrerae was analyzed for the first time and deposited in the public databases. In total, we already recovered fourteen Acaulospora species from coffee and inka nut plantations in San Martín State of Peru, suggesting that Acaulospora species are frequent and beneficial symbionts in coffee and inka nut roots in San Martín State of Peru.